2003
DOI: 10.1016/s1044-0305(02)00911-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of protein modification by 4-hydroxy-2-nonenal and other short chain aldehydes analyzed by electrospray ionization tandem mass spectrometry

Abstract: A convenient way to study lipid oxidation products-modified proteins by means of suitable model systems has been investigated. As a model peptide, the oxidized B chain of insulin has been chemically modified by either 4-hydroxy-2-nonenal (HNE) or hexanal and the extent, sites, and structure of modifications were assessed by electrospray mass spectrometry. A reduction step, using either NaCNBH 3 or NaBH 4 , was also studied to stabilize the alkylated compounds. From the data gathered, it appeared that NaCNBH 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 37 publications
3
71
0
Order By: Relevance
“…3. However, numerous attempts to detect Schiff base formation in various proteins have concluded that the extent to which HNE modifies Lys side chains is insignificant compared with the extent to which His side chains are modified (25,47,(61)(62)(63)(64)(65)(66). Moreover, immunohistochemical studies have shown that anti-HNE-His antibodies bind to amyloid plaques in AD brain tissue (26), but anti-HNE-Lys antibodies do not (36).…”
Section: Discussionmentioning
confidence: 99%
“…3. However, numerous attempts to detect Schiff base formation in various proteins have concluded that the extent to which HNE modifies Lys side chains is insignificant compared with the extent to which His side chains are modified (25,47,(61)(62)(63)(64)(65)(66). Moreover, immunohistochemical studies have shown that anti-HNE-His antibodies bind to amyloid plaques in AD brain tissue (26), but anti-HNE-Lys antibodies do not (36).…”
Section: Discussionmentioning
confidence: 99%
“…4HNE-modified lysines have also been characterized in both Schiff base and 2-pentylpyrrole forms [22,23,33]. A Michael addition to lysine or histidine residue results in a mass shift of 156.…”
mentioning
confidence: 99%
“…Most of the formed adducts are chemically reversible and only those which prove to be stable under the experimental conditions adopted will be detected. A common analytical approach includes a stabilization step by reduction with borohydride (NaBH 4 ) prior to protein digestion (240). MS studies with non-reduced peptide adducts have demonstrated that the major product ions upon tandem MS fragmentation result from the neutral loss of the aldehyde residues, difficulting the assignment of the modification site (241,242).…”
Section: Oxidation Of Non-sulphur Containing Residuesmentioning
confidence: 99%